Apigenin modulates hippocampal CREB-BDNF signaling in high fat, high fructose diet-fed rats. (May 2020) - Kalivarathan, Jagan; Kalaivanan, Kalpana; Chandrasekaran, Sathiya Priya; Nanda, Dipti; Ramachandran, Vidhya; Carani Venkatraman, Anuradha
Graphical abstract: Highlights: API improves cognitive function and insulin sensitivity. API promotes CREB-BDNF signaling. API sustains GLP-1 levels and inhibited DPP-4 enzyme. Abstract: A high-calorie diet is associated with brain insulin resistance and neuronal dysfunction. Brain-derived neurotrophic factor (BDNF) plays a role in neurogenesis, cognitive functions and synaptic plasticity. Insulin resistance significantly alters BDNF levels which makes neurons vulnerable to degeneration. Glucagon-like polypeptide (GLP)-1, an insulin secretagogue is shown to influence BDNF signaling through cAMP response element-binding protein (CREB). Apigenin (API), a naturally occurring flavone has potent antioxidant and anti-inflammatory properties. Although the neuroprotective effect of API has been shown in some studies, the effect of API on brain insulin resistance and on BDNF-CREB signaling still remains elusive. The aim of this study is to evaluate the effect of API on behavioral changes, insulin signaling and CREB-BDNF axis in hippocampus of high fat, high fructose diet (HFFD)-fed rats. The underlying mechanisms were elucidated using sitagliptin (STG), an inhibitor of dipeptidyl peptidase (DPP)-4 as a standard drug for comparison. Our results show that API has significant inhibitory potential against DPP-4 comparable to STG. Administration of API significantly improved GLP-1 levels, cognitive function, insulin signaling and influenced the CREB-BDNF axis. Chromatin immunoprecipitation (ChIP) assay revealed that the binding of CREB protein to the promoter IV of the BDNF gene is increased in API treated animals. Our findings suggest that API could modulate brain insulin signaling during calorie excess by upregulating BDNF signaling through its ability to enhance GLP-1.